2016
DOI: 10.1177/1071100716670403
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Triple and Double Osteotomies for the Treatment of Hallux Valgus

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Minimally invasive surgery (MIS), also known as percutaneous surgery, has experienced a sustained growth for the treatment of foot and ankle problems, especially over the last decade. This is supported by numerous studies including clinical series, 3,5,6,8,11,15,18,20,28,33 comparative studies, 7,22,23,38 technical reports 27,41 and radiologic validations. 17…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Minimally invasive surgery (MIS), also known as percutaneous surgery, has experienced a sustained growth for the treatment of foot and ankle problems, especially over the last decade. This is supported by numerous studies including clinical series, 3,5,6,8,11,15,18,20,28,33 comparative studies, 7,22,23,38 technical reports 27,41 and radiologic validations. 17…”
mentioning
confidence: 69%
“…Although some MIS procedures do not appear to need lateral release, 4,15,24,26 others only perform the adductor tenotomy and a partial lateral capsule release. 11,34 The precise indications for those who can benefit from this procedure remain a matter of discussion. 7,25 In addition, it should be defined which patients need an adductor tendon release and which ones require an extended lateral release.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the use of minimally invasive surgical techniques (MIS) for the treatment of hallux valgus (HV), with an increasing number of published studies including clinical series, radiologic validations, cadaveric studies, comparative studies, and technical reports on MIS techniques. 1,4,[8][9][10][15][16][17][18][19][20][21]23,[26][27][28][29][30][31][32][33][34][35][36][39][40][41][42][43]45,55,[59][60][61][62][63][64]66,70 Five recent systematic reviews concluded that MIS is a safe and reliable technique for hallux valgus correction. 6,11,28,44,65 Among the procedures to treat HV, the distal chevron metatarsal osteotomy was first described in 1962 and remains a widely accepted technique.…”
Section: Introductionmentioning
confidence: 99%
“…The most important finding of the study was that the MI LR of the first MTP joint was a safe and reliable technique that was performed in cadavers without damaging any neurovascular structures or articular cartilage. Both the PATR and EPLR techniques aimed to release the adductor tendon, and they were successful in doing so without a significant Carvalho et al, 7 Martínez Nova et al, 30 Kurashige et al 22 Adductor hallucis tendon Biz et al, 4 Díaz Fernández, 15 Martinez Nova et al, 31 Cervi et al, 8 Pichierri et al 34 Adductor hallucis tendon and partial lateral capsule Scala et al 35 Phalangeal head of adductor tendon and adherences between lateral sesamoid and plantar side of the capsule De Lavigne et al 12 Adductor tendon, plantar capsule, and transverse metatarsal ligament Lee et al 23 Lateral part of the plantar plate and lateral phalangeal-sesamoid ligament Gicquel et al 18 Lateral phalangeal-sesamoid ligament and both medial and lateral suspensory ligaments Jowett et al 21 Lateral phalangeal-sesamoid ligament Lucas et al, 26 Crespo Romero et al, 10 Siclari et al, 37 Brogan et al 6 Not specified during technique description Bauer et al, 2,3 Di Giorgio et al 16 "Abductor" tendon transverse head and capsule difference (P = .85). The PATR was successful in achieving a complete release of the tendon, whereas the EPLR achieved a three-fourths release in most of the cases.…”
Section: Discussionmentioning
confidence: 99%